PENGARUH WOM, PERSEPSI KEMUDAHAN, DAN PERSEPSI RESIKO TERHADAP MINAT BELANJA KONSUMEN PADA BUKALAPAK - Sitompul, Yeni Opita; Siharis, Alkadri Kusalendra (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
This study aims to determine the effect of word of mouth, perceived convenience and risk perception on consumer spending interest in the Bukalapak application. The population of the object in this study is the residents of Janjinauli Village, amounting to approximately 800 people. The sampling technique was carried out by the random sampling method. Data analysis used in this study is by conducting interviews, observations, and literature studies. The results of this study indicate that word of mouth with an average weight of 78% perceived ease with an average weight of 80% of perceived risk on average. a weight of 85% can influence and attract consumer buying interest on the Bukalapak online shopping site. Keywords:Bukalapak 1, interest in online shopping 2,perceived convenience 3,risk perception 4,word of mouth